Carnívoros del Área de Protección de Flora y Fauna Sierra de Quila, Jalisco - Ramírez-Martínez, María Magdalena; Iñiguez-Dávalos, Luís Ignacio; Ibarra-López, Martha Pilar (THERYA, 2014)
Introduction. A central strategy for conservation in Mexico is the creation of natural protected areas. Their management requires providing adequate information on wildlife to guide the management decision process. Within the 17 protected areas that exist in Jalisco, mammal knowledge is scarce, except for three of the most studied areas in the state: Manantlán, Chamela-Cuixmala, and Primavera forest. Because of their taxonomic and ecological diversity, carnivores are an important group to evaluate protected areas and management and conservation actions. Our aim is to provide basic information on carnivores of the Sierra de Quila Flora and Fauna Protection Area, in the State of Jalisco. Method. The Sierra de Quila is part of the Physiographic Province Neo-volcanic Axis and the sub-province Sierras de Jalisco located in the central part of the state and bordered to the north by the Sierra Madre Occidental, on the northwest by the Mesa Central, and west and south by the Sierra Madre del Sur. A total of 10 field trips were performed from November 2008 to February 2010, lasting three days each. Five vegetation types were sampled using both direct and indirect methods: track searching, scent stations, and trap-cameras. Results. Of the 16 potential carnivore species for the area, 13 species of this order were recorded (81% of potential species, Table 2). The other three carnivores reported for the area were included, but they were not recorded in our study. The richest family was Felidae with four species; two of them are classified as endangered. Depending on the sampling method, gray fox (tracks), coyote (scent stations), or puma (trapcameras) was the most abundant carnivore in the area. Activity patterns shown that four species were mainly nocturnal; two of them were diurnal and two were cathemeral (day / night; Figure 2). Discussion and Conclusion. Despite the deterioration shown in some vegetation types within the area, the presence of a number of species of carnivores gives us an idea of ecosystem resilience where even species with the priority to establish conservation programs are found as the case of two cat species recorded with endangered category (P) according to NOM-ECOL-059-2010 (DOF 2010). It is necessary to continue inventory work on carnivores of this protected area, especially in the lower part of the altitudinal range and evaluate the impact of human activities in their presence and abundance.